Habakkuk 2:4b as a Prophecy of the New Covenant in Galatians 3:11 - Coxhead, Steven R. (Bulletin for biblical research, 2025)
This article argues that Paul reads Hab 2:4b contextually as part of an eschatological prophecy that establishes the new covenant doctrine of covenantal justification by faith in Jesus, which parallels the way in which righteousness was defined "by faith" (ἐκ πίστεως) during the Abrahamic age. This contrasts with how righteousness was legitimately defined "by the works of the law" (ἐξ ἔργων νόμου) under the Mosaic covenant. Paul employs the Jewish exegetical technique of gezerah shavah, linking Gen 15:6, Lev 18:5b, and Hab 2:4b, to prove his point.